Associations between expression levels of nucleotide excision repair proteins in lymphoblastoid cells and risk of squamous cell carcinoma of the head and neck. Issue 6 (25th March 2018) - Han, Peng; Liu, Hongliang; Shi, Qiong; Liu, Zhensheng; Troy, Jesse D.; Lee, Walter T.; Zevallos, Jose P.; Li, Guojun; Sturgis, Erich M.; Wei, Qingyi
Abstract : Squamous cell carcinoma of head and neck (SCCHN) is one of the most common malignancies worldwide, and nucleotide excision repair (NER) is involved in SCCHN susceptibility. In this analysis of 349 newly diagnosed SCCHN patients and 295 cancer‐free controls, we investigated whether expression levels of eight core NER proteins were associated with risk of SCCHN. We quantified NER protein expression levels in cultured peripheral lymphocytes using a reverse‐phase protein microarray. Compared with the controls, SCCHN patients had statistically significantly lower expression levels of ERCC3 and XPA ( P  = 0.001 and 0.001, respectively). After dividing the subjects by controls' median values of expression levels, we found a dose‐dependent association between an increased risk of SCCHN and low expression levels of ERCC3 (adjusted OR, 1.75, and 95% CI: 1.26‐2.42; P trend  = 0.008) and XPA (adjusted OR, 1.88; 95% CI, 1.35‐2.60; P trend  = 0.001). We also identified a significant multiplicative interaction between smoking status and ERCC3 expression levels ( P  = 0.014). Finally, after integrating demographic and clinical variables, we found that the addition of ERCC3 and XPA expression levels to the model significantly improved the sensitivity of the expanded model on SCCHN risk. In conclusion, reduced protein expression levels of ERCC3 and XPA were associated with an increased risk of SCCHN. However, these results need to be confirmed in additional large studies.